Body mass in men and women: the Russian national representative sample data - S. A. Shalnova; A. D. Deev (Кардиоваскулярная терапия и профилактика)
At the moment, obesity is a global problem, with an increasing prevalence worldwide, which could be characterized as an obesity "epidemic". The article presents the distribution of body mass index (BMI) and abdominal obesity by age and gender in a representative national sample of the Russian population. In total, 13528 people (5760 men, 7768 women) were examined (response rate 87,8%). Overweight (IMT>25 kg/m2) increased with advanced age, from 11,0% and 15,5% among 20-year-old men and women to 53,6% and 77,0%, respectively, in those aged 60 years (p<0,0001). Obesity (BMI>25 kg/m2) prevalence in women of all ages was at least 2,5 times more prevalent than that in men (among the latter, it was no higher than 15%). Similarly, among males, abdominal obesity prevalence increased with age: from 1,5% in 20-year-olds to 20,9% in those aged 80 years and older. Regardless of age, abdominal obesity prevalence among women was substantially higher than that in men, being maximal (65,2%) among 60-year-old females.